Participatory photography and undocumented migration through Mexico at the intersection of social work and anthropology. (November 2021) - Doering-White, John
This article reflects on participatory photography in the context of ethnographic fieldwork at a humanitarian migrant shelter in Central Mexico to consider broader intersections between social work and anthropology. I describe how shifting immigration enforcement trends across Mexico reconfigured my original plan for integrating participatory photography into my work as a researcher and shelter worker. Tracing these changes through three cases examples, I highlight tensions between photography as a reflection of social experience and photography as a mechanism for enacting social change. In light of recent critiques surrounding formulaic and cursory discussions of empowerment in participatory photography, I argue that unexpected shifts in research and practice strategies are themselves meaningful data, especially in uncertain policy environments.